Religious Literacy as The Future Direction of Islamic Education and The Basis of Teaching Civic Education in Pesantren - Usman, Usman (Al-madinah: Journal of Islamic Civilization, 2024)
Since religious literacy originated in Western society, it is important to first address its application in America and Europe. The teaching of the Bible in American contexts faces several serious issues, particularly in Texas public schools. These issues include anti-Semitism, sectarianism bias, the authority to interpret the Bible as God's word, understanding Judaism through a Christian lens, the Bible as a science textbook, and the Bible's role as the foundation of America. If Bible education in general continues to confront numerous issues in America, then Indonesia's issue is determining whether religion must be taught in formal education. Practically speaking, religious literacy refers to the capacity to comprehend various religious doctrines and rituals to maintain societal harmony and prevent conflicts stemming from religious differences. The significance of religious literacy and civic education in Islamic education and pesantren will be emphasized in this article. This article employs interdisciplinary methodologies to conduct qualitative research. Participant observation, in-depth interviews, and documentation studies are the approaches used to collect the data. Comparative constant and symbolic interaction are the analysis techniques used. This article concluded that teaching about religion in accordance with the religious literacy idea is far superior to placing a strong emphasis on dogma and indoctrination. The religious education policy determines whether religious literacy instruction is successful. It is necessary to reconstruct and rework the goal and methodology of religious education in the instance of Indonesia.